Superior versus anterior plate fixation for midshaft clavicular fractures – a multicentre analysis. (1st June 2022) - Buenter, I R; Kremo, V; van de Wall, B J M; Link, B-C; Galliker, B; Babst, R; Beeres, F J P
Abstract: Objective: To date it remains unclear whether superior or anterior plating is the best option for treating midshaft clavicular fractures. The aim of this study was to compare both techniques with regard to the need of implant removal due to hardware irritation or uncomforting during daily activities, to healing and to complications. Methods: This was a retrospective study on all midshaft clavicular fractures treated operatively between 2017 and 2019 in two hospitals different in respect to anterior versus superior plating for midshaft clavicular fractures in Switzerland. The primary outcome was the number of implant removal due to hardware irritation, uncomforting, weather sensitivity or the patients wish for removal, whereas the specific reason was not evaluated. Secondary outcomes were time to union, complications, re-interventions and range-of-motion during the follow-up period of at least 6-months. Results: In total 171 patients were included in the study of which 89 (52%) received anterior plating and 82 (48%) superior plating. The overall mean age was 45 years (SD 16). There was no significant difference between anterior and superior plating in the number of implant removals (39.3% versus 45.1%), infection rate (1.1% versus 1.2%), implant failure (1.1% versus 0%), non-union (1.1% and 0%) and time to union (mean 40 weeks versus 51 weeks). Ninty-four patients had a documented range of motion after a follow up from 6 up to 12 months with no significant difference in anteflexion (mean 170 degree anterior versus 178 degree superior) and abduction (mean 166 degree versus 176 degree). Conclusion: There is no significant difference between anterior and superior plating for midshaft clavicular fractures with regard to implant removal, healing, complications and shoulder function. As both treatment opinions are viable, the decision may depend on surgeons experience.